Calpains in cyanobacteria and the origin of calpains - Dominika Vešelényiová; Lenka Hutárová; Alexandra Lukáčová; Mária Schneiderová; Matej Vesteg; Juraj Krajčovič (Scientific Reports, 2022)
Abstract Calpains are cysteine proteases involved in many cellular processes. They are an ancient and large superfamily of enzymes responsible for the cleavage and irreversible modification of a large variety of substrates. They have been intensively studied in humans and other mammals, but information about calpains in bacteria is scarce. Calpains have not been found among Archaea to date. In this study, we have investigated the presence of calpains in selected cyanobacterial species using in silico analyses. We show that calpains defined by possessing CysPC core domain are present in cyanobacterial genera Anabaena, Aphanizomenon, Calothrix, Chamaesiphon, Fischerella, Microcystis, Scytonema and Trichormus. Based on in silico protein interaction analysis, we have predicted putative interaction partners for identified cyanobacterial calpains. The phylogenetic analysis including cyanobacterial, other bacterial and eukaryotic calpains divided bacterial and eukaryotic calpains into two separate monophyletic clusters. We propose two possible evolutionary scenarios to explain this tree topology: (1) the eukaryotic ancestor or an archaeal ancestor of eukaryotes obtained calpain gene from an unknown bacterial donor, or alternatively (2) calpain gene had been already present in the last common universal ancestor and subsequently lost by the ancestor of Archaea, but retained by the ancestor of Bacteria and by the ancestor of Eukarya. Both scenarios would require multiple independent losses of calpain genes in various bacteria and eukaryotes.